Effects of different exercise types on balance function in healthy older adults and Parkinson’s patients: a systematic review - Guo, Xu Bin; Tang, Lu (Frontiers in Aging Neuroscience, 2024)
ObjectiveThis study aims to compare the effects of Tai Chi, yoga, and resistance training on balance function in healthy elderly individuals and patients with Parkinson’s disease (PD). Given the well-documented benefits of these three exercise types in enhancing balance and motor function, it is crucial to assess their differential impacts.MethodsA comprehensive search was conducted across PubMed, Web of Science, Scopus, and Cochrane Library databases through December 2023. Articles were selected based on predefined criteria, screened, and evaluated by two independent researchers who also extracted study characteristics. The risk of bias was assessed using the Cochrane risk of bias tool. The primary outcome measures were the Berg Balance Scale and the Timed Up and Go test, while the secondary measure was the Unified Parkinson’s Disease Rating Scale Part III. A random effects model was employed, and heterogeneity was measured using the I2 statistic.ResultsOf the 21 studies reviewed, 9 focused on healthy older adults and 12 targeted individuals with PD. The meta-analysis showed that Tai Chi, yoga, and resistance training significantly improved balance in patients with PD compared to control groups (p < 0.00001). Resistance training was most effective in enhancing dynamic balance in healthy older adults (p = 0.003), while Tai Chi had the most significant impact on balance improvement in PD patients (p < 0.00001). Notably, interventions conducted three to four times per week, each lasting 50–60 min and continued over 12 weeks, yielded the most substantial balance improvements.ConclusionComparative analyses demonstrate that Tai Chi, yoga, and resistance training significantly enhance balance and motor function. Specifically, resistance training markedly improves dynamic balance in healthy elderly individuals, while Tai Chi shows pronounced improvements in motor function and balance for PD patients. Optimal balance improvements are achieved by performing interventions three to four times per week, with each session lasting 50–60 min, over 12 weeks.Systematic review registrationhttps://inplasy.com/, identifier INPLASY202470042.